Evaluation of the sustainability of fruit and vegetable systems with agroecological bases: explorations in the Southeast of Buenos Aires, Argentina - Zulaica, María Laura (2022)
In line with the social and environmental impacts derived from conventional production models, questions regarding the sustainability of agri-food systems are emerging worldwide. In this context, in the Buenos Aires Province (Argentina), especially in the southeast sector, alternative production experiences are gaining more and more relevance. Based on the 10 elements of agroecology—recognized by the FAO—this paper proposes a set of indicators to evaluate the sustainability of fruit and vegetable systems with agroecological bases in the District of General Pueyrredon and the area to provide inputs for decision making. The results obtained pose the challenge of advancing in participatory evaluations. It is expected that the study conducted will contribute to the sustainability of the region's agrifood systems.